Analysis of the Degree of Regional Financial Performance, Tax Effort, and Tax Buoyancy in Main Regions and City/Regency Expansion in Jambi Province - Putra, Agung Rizki; Yanto, Yanto (Trunojoyo University of Madura, 2024)
The aim of this research is to analyze financial performance, tax effort and the elasticity of tax revenue in the parent region and expansion regions in Jambi Province. The novelty of this research is that it uses three analytical tools in assessing the autonomy of parent and expansion regions. The analysis used is financial performance analysis to assess regional financial performance, regional tax effort analysis to assess regional ability to absorb tax revenues, and tax revenue elasticity analysis to assess the productivity capacity of regional tax revenues. The research method is a quantitative method using secondary data obtained from the Central Statistics Agency website, Bank Indonesia reports, as well as relevant literature.The research results state that the financial performance of the expansion regions and the parent Regency/City regions in Jambi Province is classified as non-autonomous. In terms of tax effort, the parent district/city area in Jambi Province for the 2009-2021 period is relatively high in terms of tax capacity, as well as efforts to find tax sources. Meanwhile, the district/city expansion areas in Jambi Province are classified as having high tax capacity and low effort to find tax sources. For the regional elasticity analysis, the level of elasticity of the realization of tax revenues from the parent region and the expansion regions towards GRDP at constant prices in 2010 in the Regency/City of Jambi Province during the research period on average shows an elastic category.